Gender-related differences in elite gymnasts: the female athlete triad - Weimann, E. (Journal of Applied Physiology, 2002)
High-intensity training can alter the normal pattern of pubertal development in elite gymnasts. We investigated sex hormones, the ob gene product leptin, body composition, nutrition, and eating habits in female and male elite gymnasts from national cadres to elucidate gender-related differences. Serum leptin levels were decreased, particularly in pubertal girls, and did not show the normal developmental pattern. After leptin levels were transformed into standard deviation scores, mainly pubertal female gymnasts had significantly lower values than normal controls of the same gender, pubertal stage, and body mass index. The percentage of body fat was reduced compared with a normal age-matched population in both genders but to a higher degree in female gymnasts. When leptin standard deviation scores were based on percent body fat instead of body mass index, mean values were still significantly decreased compared with those of normal controls: 1.05 in girls (P < 0.001) and 0.60 in boys (P = 0.025). In both genders, total energy consumption and nutritional intake were insufficient, although to a lesser extent in male gymnasts. Pubertal development is influenced to a different degree in female and male elite gymnasts. In contrast to their male counterparts, high-intensity training takes place during the sensitive phase of pubertal maturation in female gymnasts. Whereas the girls displayed low estrogen levels, hypoleptinemia, reduced body fat mass, insufficient caloric intake, and retarded menarche, the pubertal development of male gymnasts remained almost unaltered.